Security monitoring - Fry, Chris (Beijing ; Cambridge [Mass.] : O$1 (BReilly, s, 2009)
How does your system stand up against today's sophisticated security threats, especially those involving data theft? With this book, security experts from Cisco Systems demonstrate how you can protect your network effectively $1 (Bfirst by determining which assets you need to monitor closely, and then developing targeted strategies and user policies to protect those vital areas. Security Monitoring offers six steps to improve network monitoring, based on the authors' presentation at the Forum for Incident Response and Security Teams (FIRST) conference in 2007. By following these security steps, you will: Develop Policies: define the rules, regulations, criteria for monitoring your network Know Your Network: build knowledge of your infrastructure with network telemetry Select Your Targets: determine the subset of infrastructure to focus monitoring efforts Choose Event Sources: identify what can and should be collected from each type Feed and Tune: begin collecting data, and tune systems using contextual information Maintain and Troubleshoot: keep your security monitoring event sources online To help you understand this approach, each chapter in Security Monitoring shows how a fictional cellular phone service implements the frameworks and methods presented, with diagrams and explanations of how the company performs security monitoring. If you implement just a few of the recommendations in this book, you'll improve your monitoring and incident response capabilities significantly. If you implement all of the recommendations, you'll have a world-class security monitoring capability.s
PrefaceChapter 1 -- Getting StartedChapter 2 -- Implement Policies for MonitoringChapter 3 -- Know Your NetworkChapter 4 -- Select Targets for MonitoringChapter 5 -- Choose Event SourcesChapter 6 -- Feed and TuneChapter 7 -- Maintain Dependable Event SourcesChapter 8 -- Conclusion -- Keeping It RealDetailed OSU flow-tools Collector SetupSLA TemplateCalculating AvailabilityColophon
Includes bibliographical references and index.
1
Keywords: Computer networks -- Security measures